(untitled) (American Journal of Multidisciplinary Research and Innovation, 2022)
Code-switching exists in many countries particularly in multilingual communities such as the City of Laoag in Ilocos Norte, Philippines. The researchers ventured into the occurrence of code-switching at Mariano Marcos State University specifically the College of Teacher Education and College of Industrial Technology, looked into its effects and made some implications. Thus, after securing permission to conduct the research in the respondents’ respective institutions, the researchers recorded, transcribed and analyzed the classroom discourses to bring about the effects of code witching committed by both the instructors and the students. Using descriptive-qualitative analysis and in-depth interview (IDI), the researchers examined the effects of code-switching among Filipino college instructors and students. They also identified some implications of the effects of code-switching in Philippine college classrooms. This approach seeks to describe, decode, translate, and otherwise come to terms with the meaning of certain more or less naturally occurring phenomena in the social world. The following effects to teaching and learning were inferred: code-switching helps students to better understand directions, eradicates language barrier for a clearer instruction, promotes better understanding by students, helps them in generating a better choice, ensures semantic understanding among students, and aids the students to investigate further, to clarify, to verify, or to confirm an earlier knowledge. All of these are directed towards achieving a better performance of the teachers and students. Based on the findings, it is concluded that code switching is a big help to facilitate better teaching and learning in Philippine college classrooms.